‘Gross inefficiency and criminal negligence’: the Services Reconnaissance Department in Timor in 1943–45 and the Darwin war crimes trials in 1946 - Morris, Narrelle (Routledge, 2017)
The post-World War II Australian military war crimes trials of Japanese from 1945–51 have been criticised for using a rule of evidence considerably relaxed from the ordinary requirements of a criminal trial, one that did not require witnesses to give evidence in person. Circumstantial evidence suggests that, in relation to a trial held in Darwin in March 1946 for war crimes committed in Timor, the secretive Special Operations Australia, otherwise known as the Services Reconnaissance Department (SRD), took advantage of the rule. This article argues that the SRD did not allow their members to give evidence in person in an attempt to control and limit the dissemination of information about their operational and security failures in Timor from 1943–45. The SRD operation was adjudged by its own official historian as displaying ‘gross inefficiency and criminal negligence’. While the SRD’s failures were known to select personnel at the time, access restrictions to archival records in the post-war period, including the war crimes trials, meant that the extent of its failures and how it appeared to manage knowledge of them has not been widely known.